Partition Isoterms and HPLC analysis o ethoxylated alkylphenol surfactant mixtures - Subero, Naudis; Bauza, Roberto; Cáceres, Ana; Ysambertt, Freddy; Márquez, Nelson (Ciencia)
Â The partition isotherms of surfactants in the oil-water system over the entire cancentration range veloiw the CMC was detemined. A normal-phase method for the separation of higher ethylene oxide number (EON) oligomers by High Performance Liquid Chromatography (HPLC) is described. Isocratic HPLC with mixed sent on silica column allows to separate oligomers up to EON=18. Gradient programming moves the limit up to EON=20. For higher EON values (up to 50) a NH2 column has to be used, either with isocraticor or gradient made. Detection was performed using UV detector.